Fractional order modelling of omicron SARS-CoV-2 variant containing heart attack effect using real data from the United Kingdom. (April 2022) - Özköse, Fatma; Yavuz, Mehmet; Şenel, M. Tamer; Habbireeh, Rafla
Highlights: A fractional order COVID-19 model is developed to examine the spread of it with and without OMICRON variant. The relationship of Omicron SARS-CoV-2 variant with heart attack using real data from the United Kingdom has been investigated. By using least-squares curve fitting technique (LCM), the fitting of the parameters is implemented. The sensitivity analysis of the parameters according to the reproduction number is given. The memory trace and hereditary traits are taken into consideration. Abstract: In this study, a new approach to COVID-19 pandemic is presented. In this context, a fractional order pandemic model is developed to examine the spread of COVID-19 with and without Omicron variant and its relationship with heart attack using real data from the United Kingdom. In the model, heart attack is adopted by considering its relationship with the quarantine strategy. Then, the existence, uniqueness, positivity and boundedness of the solution are studied. The equilibrium points and their stability conditions are achieved. Subsequently, we calculate the basic reproduction number (the virus transmission coefficient) that simply refers to the number of people, to whom an infected person can make infected, as R 0 = 3.6456 by using the next generation matrix method. Next, we consider the sensitivity analysis of the parameters according to R 0 . In order to determine the values of the parameters in the model, the least squares curve fitting method, which is one of the leading methods in parameter estimation, is benefited. A total of 21 parameter values in the model are estimated by using real Omicron data from the United Kingdom. Moreover, in order to highlight the advantages of using fractional differential equations, applications related to memory trace and hereditary properties are given. Finally, the numerical simulations are presented to examine the dynamic behavior of the system. As a result of numerical simulations, an increase in the number of people who have heart attacks is observed when Omicron cases were first seen. In the future, it is estimated that the risk of heart attack will decrease as the cases of Omicron decrease.